2014
DOI: 10.1007/s13762-014-0508-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biochar and compost on soil properties and tree growth in a tropical urban environment

Abstract: Research relating to the use of organic amendments on soils has focused largely on agricultural soils, and there is a lack of information worldwide on their efficacy as amendments for urban soil management, especially in tropical urban environments. A pot experiment was conducted to assess the influence of biochar and organic compost on urban soil properties and on tree growth performance in Singapore. Biochar and compost were mixed with topsoil in different proportions, and two urban tree species commonly gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 41 publications
(38 reference statements)
2
22
1
1
Order By: Relevance
“…BCA applications and NS, in general, significantly increased stem diameter, seedling height, RDM, TFM, SDM, and QID of seedlings, in comparison with BC and CS substrates (Figure 3). These results agree with the literature, which, in general, shows strong positive growth responses of seedlings to the use of biochar in the nursery phase (Cernansky, 2015;DeLuca et al, 2015;Ghosh et al, 2015;Thomas & Gale, 2015).…”
Section: Resultssupporting
confidence: 92%
“…BCA applications and NS, in general, significantly increased stem diameter, seedling height, RDM, TFM, SDM, and QID of seedlings, in comparison with BC and CS substrates (Figure 3). These results agree with the literature, which, in general, shows strong positive growth responses of seedlings to the use of biochar in the nursery phase (Cernansky, 2015;DeLuca et al, 2015;Ghosh et al, 2015;Thomas & Gale, 2015).…”
Section: Resultssupporting
confidence: 92%
“…Considering both species, treatment BC1 + F had the most positive impact on seedlings' developmental indicators in comparison to treatment with biochar or fertilizer alone and to the control, and in most cases exceeded or was equal to higher application rates of biochar + fertilizer (BC5 + F). Similarly, Ghosh et al [44] reported that the concomitant addition of biochar and compost had a stronger effect than biochar or compost alone on growth of two native tropical species in equivalent soil type (pH: 5.5 and density: 1.6 g/cm 3 ).…”
Section: Plant Growth and Developmentmentioning
confidence: 96%
“…Contrary to earlier experimental approaches, the formation of highly fertile black anthrosols (Amazon or African Dark Earths) was not due to the presence of pure biochar but rather to the amendment of mixtures of biochar with nutrient‐rich organic matter (Glaser & Birk, ; Solomon et al , ). Some field and pot trials tested therefore the combination of biochar and compost delivering results that indicate a synergy between the highly porous and recalcitrant biochar and nutrient‐rich organic substrates (Steiner et al , ; Schulz et al , ; Ghosh et al , ; Kammann et al , ; Vandecasteele et al , ). Prost et al () showed that biochar was enriched in nitrate, phosphate and other potential plant nutrients during the composting process.…”
Section: Introductionmentioning
confidence: 99%